Organic carboxylate material as well as preparation method and application thereof

By preparing organic carboxylate materials with high conjugation structures, and using the inorganic salt of the transition metal element in the fourth cycle for salting, the problem of insufficient specific capacity and rate performance of organic electrode materials is solved, and high specific capacity and excellent cycles are achieved performance.

CN119118822APending Publication Date: 2024-12-13SHANGHAI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411265125.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Organic electrode materials have lower specific capacity in electrochemical reactions, poor rate performance, slow reaction kinetics, and low utilization rate of active sites, resulting in insufficient electrochemical performance.

Method used

Using organic carboxylate material, its raw material components include organic carboxylic acid compounds and inorganic salts containing the fourth cycle transition metal element, it is prepared by metathesis reaction, adjusts pH value and process parameters to improve the ion exchange capacity and reaction activity of the material, and forms Organic carboxylate material with high conjugation structure.

Benefits of technology

Improve the specific capacity, cyclic performance and rate performance of organic electrode materials, enhance the ion electron conductivity and cyclic stability of electrode materials, provide more available electroactive sites, reduce the dissolution rate in the electrolyte, and extend the The cycle life of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118822A_ABST
    Figure CN119118822A_ABST
Patent Text Reader

Abstract

The invention relates to an organic carboxylate material as well as a preparation method and application thereof. The organic carboxylate material comprises the following raw material components: an organic carboxylic acid compound and inorganic salt containing a fourth-period transition metal element, wherein the organic carboxylic acid compound contains four or more conjugated benzene rings. The organic carboxylate material has relatively high specific capacity, relatively good cycle performance and excellent rate capability when being applied to a positive electrode material of a lithium ion battery and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion battery electrode materials, and in particular to an organic carboxylate material and a preparation method and application thereof. Background Art

[0002] With the vigorous development of the new energy vehicle industry, the importance of energy storage equipment has become increasingly prominent. Among them, lithium-ion batteries, as core devices, have received unprecedented attention. In lithium-ion batteries, the cost of positive electrode materials accounts for more than 40% of the total battery cost, which directly determines the cost level of the battery. Therefore, the research on lithium-ion battery positive electrode materials, which is committed to reducing costs and improving performance to meet the needs of the new energy vehicle market, has become a hot topic in the current scientific research field.

[0003] Compared with inorganic electrode materials, organic electrode materials have unique advantages in electrochemical performance due to their abundant material sources, controllable costs, eco-friendliness, sustainability, and flexible molecular structures, and are therefore favored by more and more researchers. However, organic electrode materials also face some challenges, such as low conductivity, slow reaction kinetics, and low utilization of active sites. These deficiencies may lead to relatively low specific capacity in electrochemical reactions and unsatisfactory rate performance. Summary of the invention

[0004] The present application provides an organic carboxylate material and a preparation method and application thereof to solve the following technical problem: how to improve the specific capacity of an organic positive electrode material.

[0005] In a first aspect, the present application provides an organic carboxylate material, wherein the raw material components of the organic carboxylate material include:

[0006] An organic carboxylic acid compound and an inorganic salt containing a fourth period transition metal element; wherein,

[0007] The organic carboxylic acid compound contains four or more conjugated benzene rings.

[0008] Optionally, the organic carboxylic acid compound includes at least one of the following: benzophenanthrene-2,6,10-tricarboxylic acid, 5,6,11,12,17,18-hexaazanaphthalene-2,8,17-tricarboxylic acid, and 1,4,5,8,9,12-hexaazabenzophenanthrene-2,3,6,7,10,11-hexacarboxylic acid.

[0009] Optionally, the inorganic salt includes one of the following: chloride, sulfate, nitrate.

[0010] Optionally, the fourth period transition metal element includes at least one of the following: Fe, Co, and Cu.

[0011] Optionally, the molar ratio of the organic carboxylic acid compound to the metal ions in the inorganic salt is 1:(2.5-20).

[0012] In a second aspect, the present application provides a method for preparing the organic carboxylate material according to any one of the embodiments of the first aspect, the method comprising:

[0013] Using a solvent to dissolve the organic carboxylic acid compound and the inorganic salt respectively to obtain a first solution and a second solution;

[0014] The first solution and the second solution are mixed, and the pH of the mixed solution of the first solution and the second solution is adjusted to alkaline to obtain a third solution;

[0015] The third solution is subjected to a double decomposition reaction to obtain an organic carboxylate material.

[0016] Optionally, the solvent includes at least one of the following: methanol, ethanol, and dimethyl sulfoxide.

[0017] Optionally, the process parameters of the double decomposition reaction include: reaction temperature of 25°C to 120°C, and reaction time of 6h to 48h.

[0018] In a third aspect, the present application provides a positive electrode, wherein the active component of the positive electrode comprises the organic carboxylate material described in any one of the embodiments of the first aspect.

[0019] In a fourth aspect, the present application provides a lithium battery, comprising the positive electrode described in any one embodiment of the third aspect.

[0020] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0021] The organic carboxylate material provided in the embodiment of the present application, the raw material components of the organic carboxylate material include: an organic carboxylate compound and an inorganic salt containing a fourth period transition metal element; wherein the organic carboxylate compound contains four or more conjugated benzene rings. The organic carboxylate compound contains four or more conjugated benzene rings and has a highly conjugated structure, so the organic carboxylate compound has better ionic and electronic conductivity and cycle stability when used as an electrode material, thereby showing a higher specific capacity, better cycle performance and excellent rate performance, and the organic carboxylate compound is salified by using an inorganic salt containing a fourth period transition metal element through structural design, and the excellent solubility and reactivity of the metal ions formed by the fourth period transition metal element can be used to fully allow the organic carboxylate compound and the inorganic salt containing the fourth period transition metal element to perform ion exchange, so that the organic carboxylate compound has more available electroactive sites, and changes the specific surface area, redox potential and conductivity of the organic carboxylate compound, and reduces the dissolution rate of the organic carboxylate compound in the electrolyte, so that the organic carboxylate material has a higher specific capacity, better cycle performance and excellent rate performance when applied to positive electrode materials such as lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0024] Figure 1 A schematic diagram of a process for preparing an organic carboxylate material provided in an embodiment of the present application;

[0025] Figure 2 This is an electron microscope image of an organic carboxylate material provided in Example 1 of the present application;

[0026] Figure 3 This is an infrared characterization image of an organic carboxylate material provided in Example 1 of the present application;

[0027] Figure 4 A nitrogen adsorption-desorption curve of an organic carboxylate material provided in Example 1 of the present application;

[0028] Figure 5 A pore size distribution diagram of an organic carboxylate material provided in Example 1 of the present application;

[0029] Figure 6 An XRD pattern of an organic carboxylate material provided in Example 1 of the present application;

[0030] Figure 7 This is an electron microscope (SEM) image of an organic carboxylate material provided in Example 2 of the present application;

[0031] Figure 8 This is an electron microscope (SEM) image of an organic carboxylate material provided in Example 3 of the present application;

[0032] Fig. 9 A lithium ion battery provided in Example 1 of the present application has a voltage of 1.2-3.9V and a 50mA g -1 Cycling performance diagram under current density;

[0033] Fig.10 An impedance diagram of a lithium-ion battery provided in Example 1 of the present application;

[0034] Fig.11 A lithium ion battery provided in Example 1 of the present application has a voltage of 1.2-3.9V and a charge of 0.05-5Ag. -1 Rate performance diagram at different current densities;

[0035] Fig.12 A lithium-ion battery provided in Example 1 of the present application has a voltage of 1.2-3.9V, 5Ag -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0037] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0038] In this application, the terms "include", "comprises", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0040] In a first aspect, the present application provides an organic carboxylate material, wherein the raw material components of the organic carboxylate material include:

[0041] An organic carboxylic acid compound and an inorganic salt containing a fourth period transition metal element; wherein,

[0042] The organic carboxylic acid compound contains four or more conjugated benzene rings.

[0043] In the embodiments of the present application, the organic carboxylic acid compound contains four or more conjugated benzene rings and has a highly conjugated structure, so the organic carboxylic acid compound has better ionic and electronic conductivity and cycle stability when used as an electrode material, thereby exhibiting a higher specific capacity, better cycle performance and excellent rate performance, and the organic carboxylic acid compound is salified by using an inorganic salt containing a fourth period transition metal element through structural design, and the excellent solubility and reactivity of the metal ions formed by the fourth period transition metal element can be utilized to fully allow the organic carboxylic acid compound and the inorganic salt containing the fourth period transition metal element to undergo ion exchange, thereby allowing the organic carboxylic acid compound to have more available electroactive sites, and changing the specific surface area, redox potential and conductivity of the organic carboxylic acid compound, and reducing the solubility of the organic carboxylic acid compound in the electrolyte, so that the organic carboxylate salt material has a higher specific capacity, better cycle performance and excellent rate performance when applied to positive electrode materials such as lithium ion batteries.

[0044] In some embodiments, the organic carboxylic acid compound includes at least one of: triphenylene-2,6,10-tricarboxylic acid, 5,6,11,12,17,18-hexaazanaphthalene-2,8,17-tricarboxylic acid, and 1,4,5,8,9,12-hexaazatriphenylene-2,3,6,7,10,11-hexacarboxylic acid.

[0045] In an embodiment of the present application, the above-mentioned organic carboxylic acid compound can be one or more of benzophenone-2,6,10-tricarboxylic acid, 5,6,11,12,17,18-hexaazanaphthalene-2,8,17-tricarboxylic acid, and 1,4,5,8,9,12-hexaazabenzophenone-2,3,6,7,10,11-hexacarboxylic acid. Further, the above-mentioned organic carboxylic acid compound can be 5,6,11,12,17,18-hexaazanaphthalene-2,8,17-tricarboxylic acid.

[0046] In some embodiments, the inorganic salt comprises one of the following: chloride, sulfate, nitrate.

[0047] In the embodiment of the present application, the above-mentioned inorganic salt can be one or more of chloride, sulfate, and nitrate.

[0048] In some embodiments, the fourth period transition metal element includes at least one of the following: Fe, Co, Cu.

[0049] In the embodiment of the present application, the fourth period transition metal element is suitable for the field of lithium batteries, has a moderate relative molecular mass, and has a high specific capacity. The fourth period transition metal element can be one or more of Fe, Co, and Cu.

[0050] Furthermore, the fourth period transition metal element may be Co. Co ions formed by Co metal elements have more advantages in solubility and reaction activity.

[0051] In some embodiments, the molar ratio of the organic carboxylic acid compound to the metal ions in the inorganic salt is 1:(2.5-20).

[0052] In the embodiment of the present application, the molar ratio of the organic carboxylic acid compound to the metal ions in the inorganic salt is limited to 1: (2.5-20), so that the ion exchange reaction between the organic carboxylic acid compound and the inorganic salt containing the fourth period transition metal element is fully carried out, so that the prepared organic carboxylate material has more available electroactive sites, thereby achieving efficient lithium storage performance, and then obtaining an organic carboxylate material with a high specific capacity. Exemplarily, the molar ratio of the above-mentioned organic carboxylic acid compound to the metal ions in the inorganic salt can be 1: 2.5, 1: 3, 1: 4, 1: 5, 1: 6, 1: 8, 1: 10, 1: 12, 1: 14, 1: 16, 1: 18, 1: 20, etc., and further, the molar ratio of the above-mentioned organic carboxylic acid compound to the metal ions in the inorganic salt can be 1: (5-10).

[0053] In a second aspect, the present application provides a method for preparing the organic carboxylate material according to any one of the embodiments of the first aspect, Figure 1 A schematic diagram of a process for preparing an organic carboxylate material provided in an embodiment of the present application; see Figure 1 , the method comprising:

[0054] S1, using a solvent to dissolve the organic carboxylic acid compound and the inorganic salt respectively to obtain a first solution and a second solution;

[0055] In some embodiments, the solvent comprises at least one of the following: methanol, ethanol, and dimethyl sulfoxide.

[0056] In the embodiment of the present application, the above-mentioned solvent can be one or more of methanol, ethanol, and dimethyl sulfoxide.

[0057] S2, mixing the first solution and the second solution, and adjusting the pH of the mixed solution of the first solution and the second solution to alkaline to obtain a third solution;

[0058] S3, subjecting the third solution to a double decomposition reaction to obtain an organic carboxylate material.

[0059] In some embodiments, the process parameters of the metathesis reaction include: a reaction temperature of 25° C. to 120° C., and a reaction time of 6 h to 48 h.

[0060] In the embodiment of the present application, the pH of the mixed solution of the first solution and the second solution is adjusted to alkaline (8-9) to facilitate the subsequent metathesis reaction to proceed fully, and the reaction temperature in the metathesis reaction is limited to 25°C to 120°C, and the reaction time is 6h to 48h, which can promote the metathesis reaction to proceed fully and optimize the morphology of the organic carboxylate material. Exemplarily, the above reaction temperature can be 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, etc., and further, the reaction temperature can be 80°C; the reaction time can be 6h, 10h, 12h, 14h, 16h, 20h, 25h, 30h, 35h, 40h, 45h, 48h, etc. In addition, due to different sources of fourth period transition metal ions, different reaction solvents, different molar ratios of metal ions in organic carboxylic acid compounds and inorganic salts, and different reaction temperatures and times, the product organic carboxylate materials have different morphologies.

[0061] For example, the organic carboxylic acid compound uses 5,6,11,12,17,18-hexaazanaphthalene-2,8,17-tricarboxylic acid, and its preparation method includes: cyclohexane hexaketone octahydrate (1.57g, 10mmol) and 3,4-diaminobenzoic acid (2.51g, 16.5mmol) are dissolved in a 250mL three-necked reaction flask, and 100mL of acetic acid is added to dissolve, and heated to reflux at 150°C for 5h under a nitrogen atmosphere. Then filter while hot to obtain a dark green solid, wash it three times with hot acetic acid (30mL each time), and then vacuum dry the obtained solid at 100°C with potassium hydroxide for 12h. Then put the above-obtained solid into a 250mL flask with a branch mouth, add 100mL of 25% nitric acid, heat and reflux at 130°C for 3h under a nitrogen atmosphere, and then cool to room temperature. The obtained reaction solution was then poured into 300 mL of ice water, and the yellow-green solid was filtered out and washed three times with water and ethanol (30 mL each time), respectively. The obtained solid was then vacuum dried at 100° C. for 12 h to obtain 5,6,11,12,17,18-hexaazanaphthalene-2,8,17-tricarboxylic acid.

[0062] The above double decomposition reaction of 5,6,11,12,17,18-hexaazanaphthene-2,8,17-tricarboxylic acid and a Co-containing inorganic salt is performed to obtain 5,6,11,12,17,18-hexaazanaphthene-2,8,17-tricarboxylic acid cobalt salt. Unlike the hydrothermal solvothermal reaction, 5,6,11,12,17,18-hexaazanaphthene-2,8,17-tricarboxylic acid organic cobalt salt (hereinafter referred to as HANTA-Co salt) has a petal-like structure, which can promote the charge carrier mobility in the structural network, reduce resistance, and provide more available electroactive sites for efficient lithium storage. Therefore, 5,6,11,12,17,18-hexaazanaphthene-2,8,17-tricarboxylic acid cobalt salt can be further endowed with a higher specific capacity, at 50 mA g -1 After 200 cycles at the same current density, the lithium battery can still reach 273.3 mAh g -1 High capacity, while HANTA-Co salt as a positive electrode material shows excellent rate performance, at 5Ag -1 At high current density, the lithium battery still has 157.0mAh g -1 High specific capacity.

[0063] After step S3, the method further includes: cooling and rotary evaporating the organic carboxylate material to obtain a solid; washing the solid and drying it to obtain a target organic carboxylate material; wherein the washing can be performed with deionized water, ethanol and other solvents, the drying temperature is 60°C to 100°C, and 80°C can be further selected, and the drying time is 24h to 48h.

[0064] In summary, the preparation method of the organic carboxylate material is simple to operate, does not require additional specific equipment, and can achieve large-scale production.

[0065] The preparation method of the organic carboxylate material is based on the above-mentioned organic carboxylate material. The specific raw material components of the organic carboxylate material can refer to the above-mentioned embodiment. Since the preparation method of the organic carboxylate material adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.

[0066] In a third aspect, the present application provides a positive electrode, wherein the active component of the positive electrode comprises the organic carboxylate material described in any one of the embodiments of the first aspect.

[0067] The positive electrode provided in the embodiment of the present application comprises the organic carboxylate material of the first aspect, and thus has electrochemical properties such as higher specific capacity, better cycle performance and excellent rate performance. -1 After 200 cycles at the current density, the lithium battery can reach 273.3 mAh g-1 High capacity; at the same time, HANTA-Co salt as a positive electrode material showed excellent rate performance at 5A g -1 At high current density, the lithium battery still has 157.0mAh g -1 High specific capacity.

[0068] Exemplarily, the preparation method of the positive electrode includes: mixing an organic carboxylate material (hereinafter referred to as a positive electrode active material or a positive electrode active ingredient), a conductive agent, a binder and a solvent together to prepare a positive electrode material composition; directly coating the positive electrode material composition on an aluminum current collector to prepare a positive electrode plate having a positive electrode material film. Exemplarily, the preparation method of the positive electrode includes: casting an organic carboxylate material on a separate carrier to form a positive electrode active material film. The positive electrode active material film can then be separated from the carrier and laminated on an aluminum current collector to prepare a positive electrode plate (or positive electrode) having the positive electrode active material film. Among them, the above-mentioned conductive agent can be carbon black (Spuer P). Any suitable material that can be used as a conductive agent in the art can also be used; the above-mentioned binder can be polyvinylidene fluoride ("PVDF"), or any suitable material that can be used as a binder in the art can also be used; the above-mentioned solvent can be N-methylpyrrolidone (NMP), or any suitable material that can be used as a solvent in the art can also be used; the amount of the above-mentioned organic carboxylate material, conductive agent, binder and solvent can be the same as the amount commonly used in lithium secondary batteries in the art, and at least one of the conductive agent, binder and solvent can be omitted depending on the purpose and structure of the lithium secondary battery; in the above-mentioned positive electrode, the mass ratio of the organic carboxylate material active substance, the conductive agent and the binder can be 6:3:1, 7:2:1 or 8:1:1.

[0069] The positive electrode is realized based on the above-mentioned organic carboxylate material. The specific raw material components of the organic carboxylate material can refer to the above-mentioned embodiment. Since the positive electrode adopts part or all of the technical solutions of the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.

[0070] In a fourth aspect, the present application provides a lithium battery, comprising the positive electrode described in any one embodiment of the third aspect.

[0071] In the embodiment of the present application, the capacity of the lithium battery is high, and the organic carboxylate can provide more reactive sites, which helps to increase the insertion / extraction rate of lithium ions, thereby increasing the storage capacity of lithium ions in the battery; the organic carboxylate with a highly conjugated structure helps to enhance the stability of organic molecules, and can also enhance the interface stability between organic matter and electrolyte, reduce dissolution and decomposition in the electrolyte, thereby extending the cycle life of the lithium battery. The organic carboxylate can provide more charge transfer channels during the battery reaction process, accelerate the ion transfer in the electrolyte, thereby improving the rate performance of the battery and achieving rapid charge and discharge.

[0072] The lithium battery is realized based on the above-mentioned positive electrode. The specific composition of the positive electrode can refer to the above-mentioned embodiment. Since the lithium battery adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0073] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0074] Example 1

[0075] An organic carboxylate material, wherein the raw material components of the organic carboxylate material include:

[0076] Triphenylene-2,6,10-tricarboxylic acid, 5,6,11,12,17,18-hexaazanaphthalene-2,8,17-tricarboxylic acid (hereinafter referred to as HATNTA) and cobalt chloride hexahydrate; the molar ratio of HATNTA to cobalt chloride hexahydrate is 1:4.

[0077] A method for preparing an organic carboxylate material, the method comprising:

[0078] After adding 5,6,11,12,17,18-hexaazanaphthalene-2,8,17-tricarboxylic acid (hereinafter referred to as HATNTA) (516.0 mg, 1 mmol) to 40 mL of ethanol (hereinafter referred to as EtOH) and dissolving by ultrasonication, a first solution was obtained; after adding cobalt chloride hexahydrate (952.0 mg, 4 mmol) to 20 mL of methanol (hereinafter referred to as MeOH), and dissolving by ultrasonication, a second solution was obtained. The first solution was poured into a 200 mL flask, and then the second solution was slowly added dropwise until the second solution was completely added to the flask, and 6 mL of 1M ammonia water was added to obtain a third solution. Then, a double decomposition reaction was carried out at 80°C for 10 hours to obtain a fourth solution; after cooling, the green precipitate was separated by rotary evaporation, washed several times with water, ethanol and methanol, and vacuum dried at 80°C for 24 hours to obtain the final product, organic carboxylate material 1, referred to as HATNTA-Co salt.

[0079] Figure 2 This is an electron microscope image of an organic carboxylate material provided in Example 1 of the present application; see Figure 2 , indicating that the morphology of HATNTA-Co salt is a petal-like structure; Figure 3 This is an infrared characterization diagram of an organic carboxylate material provided in Example 1 of the present application; see Figure 3 , indicating that the carboxyl groups in HATNTA have been 2+ The salt was formed and the organic carboxylate material was successfully synthesized; Figure 4 This is a nitrogen adsorption-desorption curve of an organic carboxylate material provided in Example 1 of the present application; see Figure 4 , indicating that organic carboxylate materials have a larger specific surface area and more available electroactive sites; Figure 5 This is a pore size distribution diagram of an organic carboxylate material provided in Example 1 of the present application; see Figure 5 , indicating that compared with HATNTA, the molecular distance between the organic carboxylate materials formed by HATNTA-Co salt is reduced, and the pore size is mainly micropores, which is more conducive to ion and electron conduction; Figure 6 This is an XRD diagram of an organic carboxylate material provided in Example 1 of the present application; see Figure 6 , indicating that the crystal types of HATNTA-Cosalt and HATNTA are consistent.

[0080] Example 2

[0081] An organic carboxylate material, wherein the raw material components of the organic carboxylate material include:

[0082] Triphenylene-2,6,10-tricarboxylic acid, 5,6,11,12,17,18-hexaazanaphthalene-2,8,17-tricarboxylic acid (hereinafter referred to as HATNTA) and cobalt chloride hexahydrate; the molar ratio of HATNTA to cobalt chloride hexahydrate is 1:4.

[0083] A method for preparing an organic carboxylate material, the method comprising: adding HATNTA (516.0 mg, 1 mmol) to 40 mL EtOH and ultrasonically dissolving it to obtain a first solution; adding cobalt chloride hexahydrate (952.0 mg, 4 mmol) to 20 mL dimethyl sulfoxide (hereinafter referred to as DMSO), ultrasonically dissolving it to obtain a second solution. Pour the first solution into a 200 mL flask, then slowly dropwise add the second solution until the second solution is completely added to the flask, and then add 6 mL 1M ammonia water to obtain a third solution. Then, carry out a double decomposition reaction at 80° C. for 10 hours to obtain a fourth solution; after cooling, separate the green precipitate by rotary evaporation, wash it several times with water, ethanol and DMSO, and vacuum dry it at 80° C. for 24 hours to obtain the final product, organic carboxylate 2. Figure 7 This is an electron microscope (SEM) image of an organic carboxylate material provided in Example 2 of the present application; see Figure 7 , indicating that the organic carboxylate material is a solid rod-like structure.

[0084] Example 3

[0085] An organic carboxylate material, wherein the raw material components of the organic carboxylate material include:

[0086] Triphenylene-2,6,10-tricarboxylic acid, 5,6,11,12,17,18-hexaazanaphthalene-2,8,17-tricarboxylic acid (hereinafter referred to as HATNTA) and cobalt chloride hexahydrate; the molar ratio of HATNTA to cobalt chloride hexahydrate is 1:4.

[0087] A method for preparing an organic carboxylate material, the method comprising: adding HATNTA (516.0 mg, 1 mmol) to 40 mL MeOH and ultrasonically dissolving it to form a first solution; adding cobalt chloride hexahydrate (952.0 mg, 4 mmol) to 20 mL DMSO and ultrasonically dissolving it to form a second solution. Pour the first solution into a 200 mL flask, slowly dropwise add the second solution until the second solution is completely added to the flask, and then add 6 mL 1M ammonia water to obtain a third solution. Then, perform a double decomposition reaction at 80° C. for 10 hours to obtain a fourth solution; after cooling, separate the green precipitate by rotary evaporation, wash it several times with water, methanol and DMSO, and vacuum dry it at 80° C. for 24 hours to obtain the final product, organic carboxylate material 3. Figure 8 This is an electron microscope (SEM) image of an organic carboxylate material provided in Example 3 of the present application; see Figure 8, indicating that the organic carboxylate material has a block structure.

[0088] Test Case

[0089] The organic carboxylate materials and HATNTA obtained in Examples 1, 2, and 3 were used as positive electrode active components (positive electrode active components: Spuer P: PVDF = 6:3:1), and lithium sheets were used as negative electrodes. 1.0 mol L -1 LiTFSI-DOL / DME was used as electrolyte and Celgard2500 polypropylene separator was used to assemble into CR2032 button cells. The electrochemical performance was tested using a Blue Dot test system and an electrochemical workstation. At 25°C, the charge and discharge voltage range was 1.2-3.9V, and the test lithium battery was 50mA g -1 The initial specific capacity and the specific capacity after 150 cycles at the current density are shown in Table 1 below. -1 Constant current charge and discharge performance results.

[0090] Table 1 Lithium battery at 50mA g -1 Constant current charge and discharge performance results.

[0091]

[0092] As can be seen from Table 1, compared with the HATNTA organic positive electrode, the positive electrode made of the organic carboxylate material of Examples 1 to 3 of the present application is more stable, and the lithium-ion battery under the same assembly test conditions shows higher specific capacity and longer cycle stability. Compared with Examples 2-3, the organic carboxylate material with a petal sheet structure prepared in Example 1 of the present application shows higher capacity and cycle stability under the same assembly conditions of the lithium-ion battery. Fig. 9 A lithium-ion battery provided in Example 1 of the present application has a voltage of 1.2-3.9V, 50mAg -1 Cycling performance plots at current density; see Fig. 9 , indicating that in the voltage range of 1.2-3.9V, when the petal-shaped organic carboxylate material 1 (HTANTA-Co salt) prepared in Example 1 is used as the active ingredient of the positive electrode, at 50mAg -1 The initial capacity at the current density is 297 mAh g -1 After 200 cycles, it still showed 273.3 mAh g -1 The specific capacity of the cathode is 50 mAg, and the capacity retention rate is as high as 92.1%. -1 The initial capacity of the lithium-ion battery at the current density is 224.3 mAh g -1 After 100 cycles, the capacity decays rapidly. After 150 cycles, the specific capacity of the lithium-ion battery is only 149.6 mAh g-1 . Fig.10 This is an impedance diagram of a lithium-ion battery provided in Example 1 of the present application; see Fig.10 The battery impedance was 157Ω before the cycle and 124Ω after 200 cycles, indicating that the resistance of lithium batteries containing organic carboxylate materials becomes smaller after cycling, which is more conducive to the utilization of battery capacity. Fig.11 A lithium-ion battery provided in Example 1 of the present application has a voltage of 1.2-3.9V and a 0.05-5A g -1 Rate performance graph at different current densities; see Fig.11 , indicating that the petal-like organic carboxylate material (HTANTA-Co salt) exhibited excellent rate performance as the active ingredient of the positive electrode, at 5A g -1 At high current density, the lithium-ion battery still has 157.0 mAh g -1 High specific capacity, Fig.12 A lithium-ion battery provided in Example 1 of the present application has a voltage of 1.2-3.9V, 5A g -1 Cycling performance plots at current density; see Fig.12 , at 5Ag -1 After 3000 cycles at high current density, the lithium-ion battery still has a capacity of 90.1 mAh g -1 High specific capacity.

[0093] In summary, the organic carboxylic acid compound is salified using an inorganic salt containing a fourth period transition metal element, and the excellent solubility and reactivity of the metal ions formed by the fourth period transition metal element are utilized to fully allow the organic carboxylic acid compound and the inorganic salt containing the fourth period transition metal element to undergo ion exchange, thereby allowing the organic carboxylic acid compound to have more available electroactive sites, and changing the specific surface area, redox potential and conductivity of the organic carboxylic acid compound, and reducing the dissolution rate of the organic carboxylate salt in the electrolyte. When the organic carboxylate salt material is applied to a positive electrode material such as a lithium ion battery, it has a higher specific capacity, better cycle performance and excellent rate performance.

[0094] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. An organic carboxylate material, characterized in that: The raw material components of the organic carboxylate material include: An organic carboxylic acid compound and an inorganic salt containing a fourth period transition metal element; wherein, The organic carboxylic acid compound contains four or more conjugated benzene rings.

2. The organic carboxylate material according to claim 1, characterized in that The organic carboxylic acid compound includes at least one of the following: triphenylene-2,6,10-tricarboxylic acid, 5,6,11,12,17,18-hexaazanaphthalene-2,8,17-tricarboxylic acid, and 1,4,5,8,9,12-hexaazatriphenylene-2,3,6,7,10,11-hexacarboxylic acid.

3. The organic carboxylate material according to claim 1, characterized in that The inorganic salt includes one of the following: chloride, sulfate, and nitrate.

4. The organic carboxylate material according to claim 1, characterized in that The fourth period transition metal element includes at least one of the following: Fe, Co, and Cu.

5. The organic carboxylate material according to any one of claims 1 to 4, characterized in that: The molar ratio of the organic carboxylic acid compound to the metal ions in the inorganic salt is 1:(2.5-20).

6. A method for preparing the organic carboxylate material according to any one of claims 1 to 5, characterized in that: The method comprises: Using a solvent to dissolve the organic carboxylic acid compound and the inorganic salt respectively to obtain a first solution and a second solution; The first solution and the second solution are mixed, and the pH of the mixed solution of the first solution and the second solution is adjusted to alkaline to obtain a third solution; The third solution is subjected to a double decomposition reaction to obtain an organic carboxylate material.

7. The method according to claim 6, characterized in that The solvent includes at least one of the following: methanol, ethanol, and dimethyl sulfoxide.

8. The method according to claim 6, characterized in that The process parameters of the double decomposition reaction include: reaction temperature of 25° C. to 120° C., and reaction time of 6 h to 48 h.

9. A positive electrode, characterized in that: The active component of the positive electrode comprises the organic carboxylate material according to any one of claims 1 to 5.

10. A lithium battery, characterized in that: The lithium battery comprises the positive electrode according to claim 9.